Synthesis and Bioactivity of Reduced Chalcones Containing Sulfonamide Side Chains - Noreljaleel, Anwar E. M.; Wilhelm, A.; Bonnet, S. L.; van der Westhuizen, J. H. (Journal of natural products (Washington, D.C.), 2018)
The effect on the bioactivity of antibacterial sulfonamide drugs against malaria and tuberculosis via an increase of the lipid solubility groups by condensation with a reduced chalcone was investigated. Sulfonamide derivatives (8a-8d) were obtained via a 1,3-diarylpropane scaffold, prepared by reduction of the relevant chalcones, followed by the addition of a sulfonamide moiety via the Mannich and the Mannich exchange reactions. The ClogP values indicated that the lipophilicities of 8a-8d and intermediate reduced chalcones and N-alkylated reduced chalcones (5a-7a) were much higher than those of the sulfonamides (1a-1c). The N-alkylated reduced chalcone derivatives 6 and 7 exhibited the highest antimalarial (Plasmodium falciparum (NF54 strain)) activity. Addition of the sulfonamide group weakened the activity, even though some ClogP values were higher, while 1a-1c showed no activity. The reduced chalcones 5a and 5 showed potent growth inhibition of Mycobacterium tuberculosis (H37Rv strain), but the sulfonamide derivatives 8a and 8d showed no or insignificant activity (0 and 14%, respectively) against M. tuberculosis, despite high ClogP values. Thus, the possible increase in bioactivity expected from an increase in ClogP values (lipophilicity) might be counteracted by the higher molecular weight of the studied analogues.